VD_FINDINFO HC / 2018 / 577 vom 7. August 2018 - VD Tribunal cantonal (2018)
CONTRAT DE TRAVAIL, FARDEAU DE LA PREUVE, INTÉRÊT MORATOIRE, SALAIRE, INDEMNITÉ DE VACANCES | 8 CC, 102 al. 1 CO, 104 CO, 128 ch. 3 CO, 142 CO, 323 CO, 329d CO, 317 al. 2 CPC (CH)